The Role of Loyalty Programs and Perceived Value in Bank Customer: The Moderation Effect of Security and Gender - Yudi Sutarso (Universitas Hayam Wuruk Perbanas, 2025)
This study aims to develop a model to represent how LPs (loyalty programs) -policy, rewards, and usefulness of information- influence perceived value and loyalty in banking services, considering the moderating effect of perceived security and gender. Data were collected from 388 customers of two banks offering LPs in Indonesia and analyzed with partial least squares-structural equation modeling and multi-group analysis. The study validates the impact of policy and rewards on perceived value and loyalty and expands previous studies by identifying the role of security and gender. Perceived security moderates the influence of the usefulness of information on perceived value. Additionally, the study identifies significant differences in the effect of LPs by gender: the impact of policy on perceived value and loyalty is higher amongst males; rewards are a determinant of perceived value for males but of loyalty for females; and the effect of information usefulness on loyalty occurs only amongst males.